The hidden world of egg coloration: Exploring the drivers of variation in UV reflectance (2023)
Understanding how selection pressures operate at different evolutionary scales to promote diversity in various species' traits and phenotypes has long intrigued evolutionary biologists. In recent years, efforts have been made to comprehend the function of UV reflectance in avian eggs, leading to the proposal of different hypotheses. Among the most extensively studied are the UV resistance hypothesis and the egg detectability hypothesis, both of which we investigated in this study to determine to which one may explain patterns in UV reflectance and to evaluate the driving forces associated with such variation. This study is the first to take a large-scale macroecological view of eggshell UV coloration in novel data collected for over 500 avian species and analyzed using phylogenetic comparative methods. We identified the importance of brightness and the exposure of the nest in relation to the UV chroma reflected by the egg. Likewise, although we did not observe a statistically significant effect of nest type on UV reflectance, we did find patterns that, taking into account the mean UV reflectance measurements and character mapping, reveal greater support for the UV resistance hypothesis in Passeriformes and Charadriiformes, which could suggest future research. Overall, this research contributes to a deeper understanding of the mechanisms driving UV coloration in avian eggs and sheds light on the complex interplay between selection pressures and the evolution of species' traits.